Pengembangan Media Pembelajaran Website MathMart Berbasis Realistic Mathematics Education (RME) untuk Meningkatkan Pemahaman Matematis Siswa SMP - Zakiya Amalia Hartanto Putri; Heni Pujiastuti (MUST: Journal of Mathematics Education, Science and Technology, 2026)
This study aims to develop a website-based learning media called MathMart by integrating the Realistic Mathematics Education (RME) approach on Social Arithmetic material for eighth-grade junior high school students. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). Validation was conducted by three expert validators, namely media, language, and material experts, using a Likert scale 1-5 validation sheet. The validation results showed an overall average score of 92% in the very valid category, consisting of media expert 96%, language expert 92%, and material expert 86%, with all three validators stating the media can be used without revision. The practicality test through a response questionnaire from 32 students of Class VIII B SMP IT Al-Mubarok yielded a practicality score of 91.91%, categorized as very practical, while the effectiveness test using N-Gain showed an average of 0.578 in the medium category, marked by an increase in average pre-test scores from 38.02% to 73.18% on the post-test. The study concludes that the MathMart website is valid, practical, and effective as an RME-based learning media to improve the mathematical understanding of junior high school students on Social Arithmetic material.